Gadolinium–porphyrin based polymer nanotheranostics for fluorescence/magnetic resonance imaging guided photodynamic therapy. Issue 38 (21st September 2021) - Chen, Wandi; Zhao, Junkai; Hou, Mengfei; Yang, Mo; Yi, Changqing
Abstract : A simple and robust synthetic route is successfully demonstrated to prepare metalloporphyrin-based nanotheranostics for fluorescence/magnetic resonance (FL/MR) imaging guided photodynamic therapy (PDT). Abstract : Nanotheranostics for fluorescence/magnetic resonance (FL/MR) dual-modal imaging guided photodynamic therapy (PDT) are highly desirable in precision and personalized medicine. In this study, a facile non-covalent electrostatic interaction induced self-assembly strategy is developed to effectively encapsulate gadolinium porphyrin (Gd-TCPP) into homogeneous supramolecular nanoparticles (referred to as Gd-PNPs). Gd-PNPs exhibit the following advantages: (1) excellent FL imaging property, high longitudinal relaxivity (16.157 mM −1 s −1 ), and good singlet oxygen ( 1 O2 ) production property; (2) excellent long-term colloidal stability, dispersity and biocompatibility; and (3) enhanced in vivo FL/MR imaging guided tumor growth inhibition efficiency for CT 26 tumor-bearing mice. This study provides a new strategy to design and synthesize metalloporphyrin-based nanotheranostics for imaging-guided cancer therapy with enhanced theranostic properties.